Prediksi Penawaran Mata Kuliah Studi Kasus Prodi Informatika Universitas Kristen Duta Wacana - Bastian, Brian; Anggia Rini, Maria Nila; Saputra, Laurentius Kuncoro Probo (Journal of Software Engineering and Multimedia (JASMED), 2023)
For taking a course, students are required to make a schedule so that the courses to be taken can be according to their choice. There are several obstacles when taking courses, for example when the number of students taking a course is more than the capacity estimated by the campus, so that the classes that are opened are not sufficient. Therefore, a prediction system is needed that can display how many classes are recommended to be opened and the number of students who are likely to take those classes. In the process of making the prediction system, the first thing to do is to determine what features will be used. These features are then applied to all courses and see what combinations occur. Next is to create an algorithm based on these features in the PHP programming language. Prior to that, data from any table in the database was determined beforehand to be processed so that the system could run properly and accurately. The next step is to make input available to users who can determine the minimum number of repeat students, class capacity, lab capacity, and predicted semester. The results of the research conducted and the system created allow it to predict courses based on the features that have been entered. The data used in the database is also the most recent, so the amount issued to the prediction system is an accurate amount. This system can be said to be successful because it can display recommended courses along with the number of students who are repeating and students who have not taken those courses.